Physical Work-load in Tree Felling and Cross Cutting Operations (A Case Study in Tropical Rain Forests of the West Coast) - Maleta, B. P.; Sood, K. G. (Indian Forester, 1984)
Forestry is a production activity which cannot be managed wltbout workers Forest management must have responsibility not only to provide favourable growing conditions and good silvieulture to tree crops, but to ensure proper working condition to the men workers in the woods. Human implication in forest management have been quite ignored. Our logging methods are manual. Age-old axe and saws are being used for felling and Cross cutting. The workers are subjected to very high physiological work-load while working with primitive tools which are often ill-maintained and ergonomically poorly designed. Work performance is a combined result of workers copacity to energy out-put, his muscle power, skill, tool and technique. Therefore, an appropriate technology has to be developed to improve efficiency of work output and reduce manual work-load. The present study has been carried out in tropical rain forests of the West-Coast in Karnataka State to find the aerobic capacity of forest workers and physiologlcal work stresses on tree felling and cross-cutting operations with traditional tools and also with improved manual tools such as raker-saw and how-saw. The results of the study are quite revealing The work capacity of workers in West-Coast forests has been found better as compared to workers in Central IndIan forests The energy costs of work can be reduced appreciably if the workers use improved hand saws than the traditional local axe and saw. It is of paramount importance that the use of improved saws should be propagated and workers much be trained in improved logging metbods.